The analysis of financial performance: the case study for Tenaga Nasional Berhad, Negeri Sembilan State / Nur Izzati Adzmi - Adzmi, Nur Izzati (Faculty of Business and Management, 2011)
This study was carried out to determine and analyze financial performance for Tenaga Nasional Behad (TNB) in Negeri Sembilan State from year 2005 to year 2010. TNB is the national electricity utility company, a corporate entity established in 1990. It holds a monopoly on electricity generation, transmission and distribution in Peninsular Malaysia.TNB currently services about four million customers, including industrial, commercial, mining and domestic clients. Different tariff rates are imposed on different categories of clients. The objectives of this study are to determine which year is contributing more profit to the company and to identify the financial of the performance by the company during the year studied. To analyze this company’s financial performance, financial ratios and common-size analysis were used and calculated based on the information disclosed on the financial statement of the companies in Annual Report. The study identifies the financial strength on certain criteria. Six types of ratios were selected and constructed. Each ratio represents the major categories namely liquidity, profitability, operating, asset utilization, leverage ratio and market measures. The overall findings of the study indicate that for the 5 years financial year performance, TNB marked a challenging but also rewarding year for TNB. Despite external market pressures, TNB leveraged on the electricity demand growth sparked by the recovering domestic economy as well as enhanced operational efficiencies to deliver a stronger financial performance. In conclusion, the most profitable year is recorded in year 2007 .Despite the many challenges faced by the local energy industry for the year under review, TNB rose to the occasion. TNB posted a record higher net profit and these achievements are testament of TNB commitment to the GLC transformation efforts advocated by the Government.